1995
DOI: 10.1111/j.1365-2230.1995.tb01279.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA antigens in Omani patients with vitiligo

Abstract: Fifty native Omanis with vitiligo were studied to compare the incidence of HLA ABC and DR antigens with a control population. HLA Bw6 was found in 82% of patients compared with 49% controls (Pc = 0.0009 RR = 4.56) and HLA DR7 occurred in 40% of patients and 9% in controls (Pc = 0.00075 RR = 6.17). HLA DR7 was significantly increased in those patients with acrofacial, compared to focal disease (57% vs. 24% P = 0.038). Sixty-six per cent of the patients in this study had parents who were consanguineous and a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 13 publications
2
27
1
Order By: Relevance
“…HLA typing was performed using a modified two-stage cytotoxicity technique with ethidium bromide/acridine orange staining and observation with a semi-automated fluorescent microscope. 1 The following serological specificities could be determined (76 in total): For Class II DNA typing, the DNA was extracted from 2 mL of EDTA blood using either a commercial kit (Nucleon, Scotlab, UK) or a local method using a rapid mini salting out technique described by Miller et al 4 The separated DNA was incubated in a thermal cycler with Class II primers defining DRß and DQß alleles (Dynal lowresolution sequence-specific primers, Dynal, Skoyen, Norway), together with polymerase chain reaction (PCR) buffer, taq polymerase and DNA nucleotides (Gibco BRL, Paisley, UK). The products were run on 1.2% agarose gels containing ethidium bromide, examined under UV illumination and the Class II specificities were identified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HLA typing was performed using a modified two-stage cytotoxicity technique with ethidium bromide/acridine orange staining and observation with a semi-automated fluorescent microscope. 1 The following serological specificities could be determined (76 in total): For Class II DNA typing, the DNA was extracted from 2 mL of EDTA blood using either a commercial kit (Nucleon, Scotlab, UK) or a local method using a rapid mini salting out technique described by Miller et al 4 The separated DNA was incubated in a thermal cycler with Class II primers defining DRß and DQß alleles (Dynal lowresolution sequence-specific primers, Dynal, Skoyen, Norway), together with polymerase chain reaction (PCR) buffer, taq polymerase and DNA nucleotides (Gibco BRL, Paisley, UK). The products were run on 1.2% agarose gels containing ethidium bromide, examined under UV illumination and the Class II specificities were identified.…”
Section: Methodsmentioning
confidence: 99%
“…Three recent studies from this department have given limited information in relation to disease association. [1][2][3] We describe here the results of a study on 321 Omanis studied by HLA serology, 126 of which were also investigated for Class II DNA polymorphisms. The results are compared with HLA antigen frequencies recorded from Kuwait and Saudi Arabia.…”
mentioning
confidence: 99%
“…Several studies have reported associations of vitiligo with certain HLA specificities, but no consistent association with any of the HLA class I or class II alleles has been reported. [144][145][146][147] Recently, the CTLA4 3ЈUTR polymorphism was investigated for association with disease in 74 UK patients with vitiligo 148 (Table 3). The frequency of the 106 bp allele was only increased in a subgroup of vitiligo patients suffering from an additional autoimmune disease, suggesting that vitiligo susceptibility by itself is not influenced by the CTLA4 3ЈUTR polymorphism.…”
Section: Vitiligomentioning
confidence: 99%
“…Several studies based on the serological typing of HLA have shown that the association of HLA antigens with vitiligo varies among different ethnic groups. For example, HLA associations with vitiligo include HLA‐DR4 in Caucasian Americans, 1 DR4 and DQw3 in black Americans, 2 DR4 and DR6 in a Dutch caucasoid population, 3,4 DR7 and DQw3 in north Italians, 5,6 DR7 in Omanis, 7 DR53 in the Kuwaiti population 8 and DRw12 in north Germans 9 . Negative associations of DR3 and DR52 were observed in north Italians 5 .…”
mentioning
confidence: 99%